Self-reported emotional eating is not related to greater food intake: results from two laboratory studies. Issue 4 (2nd April 2020) - Braden, Abby; Emley, Elizabeth; Watford, Tanya; Anderson, LaNaya; Musher-Eizenman, Dara
Abstract: Objective : Despite widespread use of emotional eating self-report measures, the validity of these measures has been questioned. Most of this research has focused on the validity of the Dutch Eating Behavior Questionnaire (DEBQ) as opposed to the Emotional Eating Scale (EES). The current paper describes two experimental studies that examined associations between self-reported emotional eating and emotional eating measured in the laboratory. To address previous design limitations, the current studies used highly palatable foods, effective mood induction methods, and the EES, in addition to the DEBQ. Design : In two samples of college students, participants were randomised to a neutral or negative mood induction. Main Outcome Measures : The traditional DEBQ and the original and revised versions of the EES were used to measure self-reported emotional eating. Emotional eating was assessed in the laboratory using a bogus taste test. Subjects were asked to taste various foods, and food intake was measured. Results : In both samples, self-reported emotional eating using the DEBQ and EES was unrelated to laboratory measured emotional eating (i.e. food consumed during the bogus taste test). Conclusion : Future research in this area would benefit from using diverse samples and development of novel methods of assessing emotional eating.